2017
DOI: 10.1021/acs.analchem.7b00947
|View full text |Cite
|
Sign up to set email alerts
|

One Step Forward for Reducing False Positive and False Negative Compound Identifications from Mass Spectrometry Metabolomics Data: New Algorithms for Constructing Extracted Ion Chromatograms and Detecting Chromatographic Peaks

Abstract: False positive and false negative peaks detected from extracted ion chromatograms (EIC) are an urgent problem with existing software packages that preprocess untargeted liquid or gas chromatography-mass spectrometry metabolomics data because they can translate downstream into spurious or missing compound identifications. We have developed new algorithms that carry out the sequential construction of EICs and detection of EIC peaks. We compare the new algorithms to two popular software packages XCMS and MZmine 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
265
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(292 citation statements)
references
References 33 publications
1
265
0
2
Order By: Relevance
“…Centroided mass detection was done keeping the noise level at 1 and 0.01 for MS1 and MS2, respectively. Chromatograms were built using the ADAP algorithm (Myers et al 2017) by inputting the following parameters: intensity threshold of 5.0, minimum highest intensity of 5.0 and m/z tolerance of 10 ppm. Chromatogram deconvolution was done using ADAP algorithm, and chromatograms were deisotoped.…”
Section: Lc-hr-ms/ms Data Processing and Analysismentioning
confidence: 99%
“…Centroided mass detection was done keeping the noise level at 1 and 0.01 for MS1 and MS2, respectively. Chromatograms were built using the ADAP algorithm (Myers et al 2017) by inputting the following parameters: intensity threshold of 5.0, minimum highest intensity of 5.0 and m/z tolerance of 10 ppm. Chromatogram deconvolution was done using ADAP algorithm, and chromatograms were deisotoped.…”
Section: Lc-hr-ms/ms Data Processing and Analysismentioning
confidence: 99%
“…We started the workflow development by defining the problems of peak detection. Myers et al have shown, that, when applied to the same dataset, different peak picking algorithms return two different yet overlapping peak sets [9,13]. To assess the performance of a peak picking algorithm, we must also consider the true peak set, which is unknown.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, this is commonly achieved by using one of a number of software options on the market e.g. XCMS [5], metaMS [6], MetAlign [7], mzMine [8], ADAP-GC [9,10], PyMS [11] and eRah [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The converted dataset can be processed with various peak picking software tools, such as MZmine 19,21 , XCMS 20 , or OpenMS 25 . Due to its open-source modular framework, MZmine 2 has seen multiple extensions implemented by various different laboratories in the past years, which include feature detection algorithms [26][27][28] , molecular networking 29,30 , visualization techniques 31,32 , as well as compound identification algorithms 33,34 , making the overall toolbox almost ready for GC-TOF MS data mining of complex archaeological sample sets, as recently shown by Decq et al 35 . Since electron ionisation (EI) results in numerous fragments, which provide information about the molecular structure, spectra matching was the choice for compound identification.…”
Section: Optimization Of a Lc-ms Metabolomics Data Mining Workflow Fomentioning
confidence: 99%